2006
DOI: 10.1093/annonc/mdl105
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the use of somatostatin analogs as antitumor agents

Abstract: While the rationale exists for the use of somatostatin analogs as antitumor agents, studies are ongoing to identify analogs with activity across the range of receptor subtypes to maximize the potential of such treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
191
0
23

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(218 citation statements)
references
References 93 publications
4
191
0
23
Order By: Relevance
“…As octreotide is also known to have indirect effects, such as central effects on GH release and proposed effects on angiogenesis (Susini & Buscail 2006) that may modulate in vivo growth, we next evaluated the effect of octreotide and rapamycin, alone and in combination, in mice bearing BON xenografts. BON cells were injected into the upper right flanks of male BALB/c mice, and 8 days after inoculation, mice were divided into six groups and treated with long-acting octreotide (Sandostatin LAR) alone (30 mg/kg), octreotide vehicle, rapamycin alone (15 mg/kg), rapamycin vehicle DMSO, rapamycin and octreotide, and combination vehicle.…”
Section: Rapamycin and Octreotide Antitumor Activity In Vivomentioning
confidence: 99%
“…As octreotide is also known to have indirect effects, such as central effects on GH release and proposed effects on angiogenesis (Susini & Buscail 2006) that may modulate in vivo growth, we next evaluated the effect of octreotide and rapamycin, alone and in combination, in mice bearing BON xenografts. BON cells were injected into the upper right flanks of male BALB/c mice, and 8 days after inoculation, mice were divided into six groups and treated with long-acting octreotide (Sandostatin LAR) alone (30 mg/kg), octreotide vehicle, rapamycin alone (15 mg/kg), rapamycin vehicle DMSO, rapamycin and octreotide, and combination vehicle.…”
Section: Rapamycin and Octreotide Antitumor Activity In Vivomentioning
confidence: 99%
“…Even before its approval, case reports suggested that octreotide showed antitumor properties for patients with NETs [18,19]. Reviews of preclinical studies suggest direct receptor-mediated antitumor effects of cell cycle inhibition, growth factor inhibition, and proapoptotic activity [20,21]. Furthermore, there may be indirect effects, including inhibition of the release of growth factor and trophic hormones, inhibition of angiogenesis, and modulation of the immune system [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, consistently with the model of glucocorticoid-mediated down-regulation of sstr2, pretreatment of AtT20 cells with dexamethasone abolished the inhibitory effects of octreotide on ACTH secretion, but had no effect on the inhibitory action of pasireotide or somatostatin-14 [70]. Somatostatin analogues may also confer an indirect anti-proliferative effect through inhibition of angiogenesis (down-regulation of vascular endothelial growth factor), which limits tumour growth [74], and by reducing levels of growth factors and trophic hormones [74].…”
Section: Emerging Drugs For Cushing's Diseasementioning
confidence: 88%